1989
DOI: 10.30972/bon.62-31507
|View full text |Cite
|
Sign up to set email alerts
|

Relaciones genómicas entre cuatro especies diploides de Turnera con flores amarillas (serie Canaligerae)

Abstract: <div>Los rasgos morfológicos y citogenéticos de los híbridos artificiales entre cuatro especies diploides (2n = 10): <em>T.concinna, T.Krapovickasii, T.scabra </em>y<em> T.subulata</em> han sido estudiados. Los híbridos fueron intermedios en varios caracteres, como el color de las flores, la longitud, la anchura y forma de las semillas, en algunos rasgos se parecían a uno o al otro padre. Todos los híbridos interespecíficos mostraron un alto porcentaje de PMC con cinco bivalentes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
17

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 2 publications
2
17
0
17
Order By: Relevance
“…Heavy lines indicate the evolution of homostyly. their genomes have been given different designations based upon karyotypic differences (Fernández and Arbo, 1989Arbo, , 1990Arbo, , 1993aArbo, , b, 1996. The white/blue-flowered species have the ''C'' genome, while the yellow-flowered species possess variants of the ''A'' genome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy lines indicate the evolution of homostyly. their genomes have been given different designations based upon karyotypic differences (Fernández and Arbo, 1989Arbo, , 1990Arbo, , 1993aArbo, , b, 1996. The white/blue-flowered species have the ''C'' genome, while the yellow-flowered species possess variants of the ''A'' genome.…”
Section: Discussionmentioning
confidence: 99%
“…The only cross reported for this species was between distylous T. grandiflora and T. candida. A resulting hybrid was long-styled, but no information on compatibility relationships was obtained (Fernández and Arbo, 1996). It is not clear whether T. candida has had an origin comparable with the putative recombinant origins of homostyly observed among the yellow-flowered polyploid species (Barrett and Shore, 1987;Tamari et al, 2001).…”
Section: Evolution Of Base Chromosome Number-three Different Base Chrmentioning
confidence: 93%
“…The polyploids all appear to be allopolyploids based upon examination of meiosis in these species, although Fernández & Arbo (2000b) have suggested that octaploids Turnera aurelii and Turnera cuneiformis , and hexaploids Turnera orientalis , T. ulmifolia var. ulmifolia and T. velutina may be segmental allopolyploids based upon studies of meiosis in hybrids (Fernández & Arbo, 1993a, 2000a,b; Fernández, 1997). Turnera candida Arbo is the only known self‐compatible diploid homostylous species in this series (Fernández & Arbo, 1996).…”
Section: Polyploidy and Breeding Systemsmentioning
confidence: 99%
“…ulmifolia and T. velutina may be segmental allopolyploids based upon studies of meiosis in hybrids (Fernández & Arbo, 1993a, 2000a,b; Fernández, 1997). Turnera candida Arbo is the only known self‐compatible diploid homostylous species in this series (Fernández & Arbo, 1996). The nature of homostyly is unknown in this species since compatibility relationships (Fig.…”
Section: Polyploidy and Breeding Systemsmentioning
confidence: 99%
See 1 more Smart Citation